Lighthouse Jetty, Trinidad. - (:unkn) unknown (Davidson-Todd. Ltd., 2011)
Here is a picture of the Port of Spain harbour, lighthouse with Customs Office and St. Vincent Jetty. People are walking about on the jetty and boats are docked.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Boats and boating--Trinidad and Tobago; Lighthouses--Trinidad and Tobago; Harbors--Trinidad and Tobago; Customhouses--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Docks--Trinidad and Tobago; Jetties--Trinidad and Tobago; Mountains--Trinidad and Tobago; [1910]; Ports of entry--Trinidad and Tobago; Public buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Ships--Trinidad and Tobago